Au-delà de la ¡ Revolución ! - Julien Rebotier (EchoGéo)
The “Bolivarian Revolution” rises at the end of a century of huge transformations for the country as regards oil exploitation. This still has a lot of consequences today. The election of President is the product of both the failure of a negotiated democracy and two decades of crisis which sharpen inequalities. Nevertheless, both the socio political order and symbolic order can be questioned, but economic order is not really modified. Chavism changes part of the face of Venezuela, affects regional geopolitics on different degrees, but shows some difficulties to make radical changes come true. The worrisome drift of authoritarianism is still potential.